2011
DOI: 10.4049/jimmunol.0903207
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 Receptor Is Critical for the Development of Memory B Cell Responses

Abstract: Development of long-term humoral immunity, characterized by the formation of long-lived plasma cells (PCs) in the bone marrow and memory B cells, is a critical component of protective immunity to pathogens, and as such it is the major goal of vaccination. However, the mechanisms involved in the generation of long-term humoral immunity remain poorly understood. In this study, we used IL-21R–deficient (IL-21R.KO) mice to examine the role of the IL-21 pathway in the development of the B cell memory response. Prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 43 publications
4
58
1
1
Order By: Relevance
“…IL-21 promotes the expansion and antitumor activity of NK cells, enhances CD8 T cell maturation into CTLs, and promotes the differentiation and expansion of T FH cells while downregulating regulatory T cells (2,(4)(5)(6)(7)(8). Within the B cell lineage, IL-21 regulates B cell proliferation and survival, Ig production and class switching, germinal center formation, plasma cell differentiation, and memory B cell responses (9)(10)(11)(12).…”
Section: Nterleukin-21 Is a Member Of The Type I Cytokine Family Wimentioning
confidence: 99%
See 1 more Smart Citation
“…IL-21 promotes the expansion and antitumor activity of NK cells, enhances CD8 T cell maturation into CTLs, and promotes the differentiation and expansion of T FH cells while downregulating regulatory T cells (2,(4)(5)(6)(7)(8). Within the B cell lineage, IL-21 regulates B cell proliferation and survival, Ig production and class switching, germinal center formation, plasma cell differentiation, and memory B cell responses (9)(10)(11)(12).…”
Section: Nterleukin-21 Is a Member Of The Type I Cytokine Family Wimentioning
confidence: 99%
“…To further characterize this defect, we assessed whether the kinetics of donor CD8 T cell engraftment and expansion are altered in the absence of IL-21R signaling. In aGVHD, donor CD8 T cells undergo three phases: activation and expansion of naive cells (days 0-7), followed by expansion of mature effector CTLs (days 7-10) and downregulation and contraction of effector T cells (days [10][11][12][13][14]. The kinetics of donor CD8 expansion and contraction progressed similarly in IL-21R-sufficient and -deficient donor CD8 cells, with the peak effector number reached on day 10, followed by their contraction by day 14 in both groups (Fig.…”
Section: P→f1 Agvhd Induced With Il-21r-deficient Donor T Cells Displmentioning
confidence: 99%
“…Bien que le but premier de ces études n'était pas d'étudier l'impact de l'IL-21 sur la réponse humorale, une réduction significative de la production d'anticorps spécifiques du LCMV a été observée chez les souris KO pour l'IL-21R suite à l'infection par la souche immunosuppressive (clone 13). Ces observations sont en accord avec le rôle clé joué par l'IL-21 dans la génération des plasmocytes et la production d'anticorps par ces derniers [3,20]. Les souris KO pour l'IL-21R produisent des anticorps de faible affinité ou non spécifiques du virus.…”
Section: Revuesunclassified
“…Indeed, IL-21R KO mice have reduced antigen-specific IgG antibody responses 7-10 days following immunization with numerous T cell-dependent (TD) antigens [36]. However, IL-21R KO mice have been reported to generate normal IgG antibody responses to Salmonella, which elicits a completely extrafollicular antibody response, and long-term IgG antibody responses to some TD antigens, indicating that the requirement for IL-21 for isotype switching and plasma cell differentiation to foreign antigens is not absolute [50][51][52].…”
Section: Regulation Of Antibody Pesponsesmentioning
confidence: 99%
“…IL-21 has also been reported to directly drive the differentiation of TFH and GC B cells through the induction of the transcription factor Bcl-6 [50,52]. However, the requirement for IL-21 in TFH and GC B cell development appears to be dependent on the time points examined and the immunogens used [51,52,54,55]. Studies using virus-like particles demonstrated that stimulation of B cells by TLR ligands may overcome the need for IL-21 mediated signals in GC formation [55].…”
Section: Regulation Of Antibody Pesponsesmentioning
confidence: 99%